Tissue Engineering In Vitro Leaflet- and 3-Dimensional Printing-Based Implant Prototypes for Infant Mitral Valve - Martha I. González-Duque; Arielle Breuninger; Frédéric Leis; Julio B. Michaud; Shaginth Sivakumar; Vincent Pautu; Marisa E. Jaconi; Marc Jobin; Adrien Roux (BME Frontiers)
Objective: This study engineers leaflet- and 3-dimensional (3D) printing-based implant prototypes for infant mitral valve repair via in vitro cultured mesoangioblasts isolated from the human fetal aorta (AoMAB). Impact Statement: Ultrahigh-molecular-weight polyethylene (UHMWPE) coatings, as well as 3D-printed gelatin methacrylate (GelMA) hydrogels for implants, represent new possibilities for devices used in mitral valve repair. Introduction: Mitral valve prolapse (MVP) repair in pediatric patients is challenging due to somatic growth, patient–prosthesis mismatch, reinterventions, infections, and thromboembolism. Tissue-engineered heart valves (TEHVs) offer potential solutions through conventional and 3D printing biofabrication. Methods: Four materials are evaluated: UHMWPE, UHMWPE coated with polyvinyl alcohol (PVA), UHMWPE coated with PVA and collagen, and 3D-printed GelMA hydrogels. The prototypes are characterized for micro/nanostructural, physicochemical (degradation, contact angle, Fourier transform infrared spectroscopy), and mechanical properties (simple strength tests, dynamic mechanical analysis) and assessed for cytocompatibility using AoMAB cells. A 3D printing mitral valve prototype is analyzed via immunostaining. Results: Results highlight UHMWPE coated with PVA and collagen as the most promising, with degradation (7.30 ± 18.71%), a hydrophilic contact angle (26.13 ± 1.45°), and biocompatibility (177.04 ± 68.92% viability). GelMA prototypes show superior viability (216.77 ± 77.69%) and scalability for 3D printing. Conclusion: UHMWPE coated with PVA and collagen and GelMA demonstrate strong potential for TEHVs, with AoMAB cells facilitating 3D culture and future personalized pediatric applications. Further in vitro validation and thrombogenicity assessments are needed.